Urea increases fed‐batch growth and γ‐linolenic acid production of nutritionally valuable Arthrospira (Spirulina) platensis cyanobacterium. Issue 5 (2nd July 2014) - Nascimento Sassano, Carlos Eduardo; Gioielli, Luiz Antonio; Converti, Attilio; de Oliveira Moraes, Iracema; Sato, Sunao; de Carvalho, João Carlos Monteiro
<x xml:space="preserve">Abstract</x> In this article we investigate the simultaneous influence of feeding time and amount of urea added as a nitrogen source on the fed‐batch growth and composition of Arthrospira (Spirulina) platensis. Cultivations were performed in 5‐L minitanks at constant temperature (25°C) and light intensity (42 μmol photons/m2s), using exponentially increasing rate of urea addition, and varying the above independent variables in the ranges 9–15 days and 4.6–12.1 mM, respectively. Special emphasis was placed on the content of added high value fatty acids (e.g., γ‐linolenic acid) of concern for the food industry. To this purpose, a 22‐plus star central composite design was employed, and maximum cell concentration, cell productivity, yield of biomass on nitrogen added, protein content and fatty acids profile were evaluated by multiple regression analysis. The highest cell concentration (1759 mg/L) was obtained at feeding time of 14 days and amount of urea per unit reactor volume of 5.8 mM, while the highest contents of γ‐linolenic acid (27.5% of the lipid fraction) and proteins (77.2%) were obtained at 10 and 14 days and 5.8 and 10.8 mM, respectively. The results confirm the possibility of using urea as cheap nitrogen source to culture this nutritionally valuable cyanobacterium.